Miscellaneous collections [M2838-2839] - Merseyside Record Office; National Library of Australia; Australian Joint Copying Project (Canberra : Australian Joint Copying Project, 1993)
Crawford Family papers: Archibald Crawford (1869-1940) correspondence with relatives in Australia, mostly around Orange. Graham Family papers: Power of attorney of William Graham of Kemsey, McLeay River, NSW to Laura and Ellen Graham (1863).
Australian Joint Copying Project miscellaneous series M2838-2839.
Microfilm.
Original held by the Merseyside Record Office, Cunard Building, Pier Head, Liverpool L3 1EG, United Kingdom.
List available (5 p.).
Keywords: Crawford family; Graham family